Self-Control Factor Analysis, Financial Anxiety, and Financial Stress on Financial Satisfaction as an Indication Financial Sustainability - Junianto, Yopy; Radianto, Wirawan Endro Dwi (STIE Malangkucecwara, 2024)
Abstract: The focus of this research is to find out the factors that can increase financial satisfaction.Financial literacy is very important for economic growth. One aspect of financial literacy that can increase economic growth is financial satisfaction . Low levels of financial satisfaction negatively impact a person's current and future financial adequacy. This research was conducted during the COVID-19 pandemic where people experienced financial anxiety, financial stress, financial self-control. This study used these factors as predictors and the test results in this study explain that there is a significant effect association between self-control with financial satisfaction, then financial stress and financial anxiety with financial stress and financial satisfaction. These influencing factors can be aspects of further development to increase sustainable economic growth. Keywords: Self Control, Financial Anxiety, Financial satisfaction, Financial Stress